Testing charm quark thermalisation within the statistical Hadronisation model - Andronic, Anton; Braun-Munzinger, Peter; Köhler, Markus Konrad; Stachel, Johanna (Nuclear physics. A, Nuclear and hadronic physics, 2019)
A wealth of data on charmonium production in Pb-Pb collisions from the LHC experiments has provided strong evidence for (re-)generation as a dominant production mechanism at low transverse momentum. We present an important extension of the statistical hadronisation model to describe J/ψ transverse momentum distributions based on input parameters from hydrodynamical simulations. Comparison to the data allows the testing of the degree of thermalisation of charm quarks in the quark-gluon plasma. To this end we will report analyses of the J/ψ transverse momentum spectra in Pb-Pb collisions at sNN=2.76and5.02TeV.
XXVIIth International Conference on Ultrarelativistic Nucleus-Nucleus Collisions (Quark Matter 2018)
Gesehen am 21.10.2019